Microbial formulations for drought alleviation in Sunflower: Microbial formulations for drought alleviation in Sunflower - LAKSHMI PRAYAGA; P LAKSHMAMMA; C SARADA (Journal of Oilseeds Research, 2023)
An experiment was conducted with 3 microbial formulations (CRIDA resilia 1, CRIDA resilia 2 and one from NBAIM) to alleviate the drought effects on sunflower. Drought affected all the parameters except plant height, leaf number and days to flowering. Seed yield was the most affected with 58% reduction followed by LAI with 52% due to stress. Seed treatment with CRIDA resilia 2 increased seed yield in control by 35% but the same is not effective in ameliorating drought effect.